A Genetic System for Methanocaldococcus jannaschii: An Evolutionary Deeply Rooted Hyperthermophilic Methanarchaeon - Susanti, Dwi; Frazier, Mary C.; Mukhopadhyay, Biswarup (Frontiers in Microbiology, 2019)
Phylogenetically deeply rooted methanogens belonging to the genus of Methanocaldococcus living in deep-sea hydrothermal vents derive energy exclusively from hydrogenotrophic methanogenesis, one of the oldest respiratory metabolisms on Earth. These hyperthermophilic, autotrophic archaea synthesize their biomolecules from inorganic substrates and perform high temperature biocatalysis producing methane, a valuable fuel and potent greenhouse gas. The information processing and stress response systems of archaea are highly homologous to those of the eukaryotes. For this broad relevance, Methanocaldococcus jannaschii, the first hyperthermophilic chemolithotrophic organism that was isolated from a deep-sea hydrothermal vent, was also the first archaeon and third organism for which the whole genome sequence was determined. The research that followed uncovered numerous novel information in multiple fields, including those described above. M. jannaschii was found to carry ancient redox control systems, precursors of dissimilatory sulfate reduction enzymes, and a eukaryotic-like protein translocation system. It provided a platform for structural genomics and tools for incorporating unnatural amino acids into proteins. However, the assignments of in vivo relevance to these findings or interrogations of unknown aspects of M. jannaschii through genetic manipulations remained out of reach, as the organism was genetically intractable. This report presents tools and methods that remove this block. It is now possible to knockout or modify a gene in M. jannaschii and genetically fuse a gene with an affinity tag sequence, thereby allowing facile isolation of a protein with M. jannaschii-specific attributes. These tools have helped to genetically validate the role of a novel coenzyme F420-dependent sulfite reductase in conferring resistance to sulfite in M. jannaschii and to demonstrate that the organism possesses a deazaflavin-dependent system for neutralizing oxygen.